The Impact of Ethical Climate on Relationship between Corporate Reputation and Organizational Identification - ÖNCER, AYLA ZEHRA; YILDIZ ŞEN, MÜGE LEYLA (ELSEVIER SCIENCE BV, 2012)
The achievement of strategic competitive advantage largely depends on employee behavior and employee behavior then, is influenced by the strength of the organizational identification. Thus, organizational identification has been subject to so many studies in literature. Besides, corporate reputation is discussed as another outstanding factor. The purpose of this study is to examine the relationship between the perceived corporate reputation of organization and organizational identification, and how ethical climate underlines such a possible effect on this relation. The survey of this study is conducted on 228 employees of a leading multinational insurance company in Turkey. The obtained data from the questionnaires are analyzed through the SPSS statistical packaged software. Analyses results showed that corporate reputation has significant positive effects on organizational identification and this relation is moderated by two different types of ethical climate. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference.
Keywords: Ethical climate; Corporate reputation; Organizational identification; SUPERVISORY TRUST; COMMUNICATION; COMMITMENT; ATTITUDES; TURNOVER